Brief, comparative analysis of the French and Spanish legislation in terms of gender violence against women - Brox Sáenz de la Calzada, Alicia (Filanderas, 2017)
Violence against women has been legally translated in different ways. While the International Human Rights Organizations define it as any act of violence committed against a woman, merely because they are women. The State members of the European Union often restrict this concept legally, depending on several factors. This diversity means a lack of uniformity. The fact is that, there are multiple criminal solutions for the same criminal case. To limit the differences, the member states of the Council of Europe framed in 2011 the Istanbul Convention. This text of great significance urges prosecutors to follow certain gender patters when it comes to the making of laws, as it is expected to reach a greater European harmony. This paper briefly addresses the current situation of this question in France and Spain, two signatory countries of the Convention which present great legislative disparities on this matter. While Spain has introduced gender violence in its Criminal Code as an autonomous sex specific infringement, France has chosen to do it as aggravating circumstance.
Keywords: Gender violence against women; Gender perspective; Gender blindness; Conjugal violence/spousal violence; French/Spanish Criminal Law